"Far North Features Pictured by the Bartlett-Academy of Natural Sciences Expedition to Greenland" (Philadelphia Evening Bulletin, 1930)
"The Morrissey taking on a fresh supply of water from a pool on an ice flow off Shannon Island. Harry A. Whitney represented the Academy of Natural Sciences, which obtained specimens of Greenland animal life which will be mounted in a habitat group at the museum." With clipping